2017
DOI: 10.21307/acee-2017-028
|View full text |Cite
|
Sign up to set email alerts
|

On-Site Diagnostics Of The Mechanical Ventilation In Office Buildings

Abstract: The paper presents a part of project entitled "Development of thermal diagnostics of buildings", which related to reduced of energy consumption in the buildings. The detailed scope of the project is described in [1]. As part of the research task, a method of a rapid diagnosis of heating system [2], cooling sources [3] and airconditioning systems was developed as well as a method of calculate building energy performance certificates based on measurements [4]. This paper presents the research done in two office … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The last step should be diagnostic measurements that will allow an evaluation of the operation of the system in real conditions [40]. This scenario is relatively easy to implement for mechanical ventilation and an example of such diagnostics can be found in Blaszczok et al [41]. For natural ventilation, it is quite challenging to objectively assess the quality of ventilation.…”
Section: Diagnostics Of Natural Ventilation Systemsmentioning
confidence: 99%
“…The last step should be diagnostic measurements that will allow an evaluation of the operation of the system in real conditions [40]. This scenario is relatively easy to implement for mechanical ventilation and an example of such diagnostics can be found in Blaszczok et al [41]. For natural ventilation, it is quite challenging to objectively assess the quality of ventilation.…”
Section: Diagnostics Of Natural Ventilation Systemsmentioning
confidence: 99%
“…During carried out diagnostics it was found that the airtight windows do not have diffusers, which results in the lack of air flow in the exhaust ventilation system [4]. A detailed description of selected elements of mechanical ventilation is presented in the paper [17]. In practice there is only the natural ventilation in the building.…”
Section: Description Of the Studied Office Buildingmentioning
confidence: 99%
“…As a result, there has been a need for on-site diagnostics of air conditioning installations, which should include energy efficiency assessments whether it meet the requirements of the building. [4,7,8] and in the current paper, • the on-site the diagnostics of indoor environment quality, the results are presented in [4,9], • the measurement based drawing up of energy performance certificates, the results are presented in [4,[10][11][12][13]. Full diagnostics is understood as a combination of inspection and diagnostic measurements.…”
Section: S T R E S Z C Z E N I Ementioning
confidence: 99%
“…The tested cooling sources are located in two office buildings. Brief description of the construction of the buildings and the performed thermal diagnostics of the ventilation systems in these buildings is presented in the paper [8].…”
Section: Description Of the Tested Cooling Sourcesmentioning
confidence: 99%